THE ROLE OF CHANCES EQUALITY AND SOCIAL INCLUSION IN TERMS OF ECONOMIC DEVELOPMENT - GÂRDAN, Iuliana Petronela; GÂRDAN, Daniel Adrian (Annals of Spiru Haret University. Economic Series, 2016)
The article deals with the issue of equality of chances, seen from the perspective of the importance that it may have in relation to social inclusion of individuals and economic development at the level of national economy. Social integration of both women and men is a natural goal, specific to the current level of economic, social and cultural development for most countries. The active promotion of equality of chances not only at the level of legislative initiatives but also in the space of social and entrepreneurial initiatives is the most effective solution to provide a favourable framework for the development of the contemporary society. The article reviews the concepts addressed, the legislation in Romania on equality of chances, and discusses the complex relationship that exists between sustainable economic development and the promotion of equality of chances on a large scale at the level of a national economy.